Tissue and serum pepsinogen I and II in gastric cancer identified using immunohistochemistry and rapid ELISA. Issue 4 (April 1995) - Konishi, N; Matsumoto, K; Hiasa, Y; Kitahori, Y; Hayashi, I; Matsuda, H
Abstract : AIMS–To investigate the immunohistochemical expression and the serum concentrations of pepsinogen I and II in different histological types of gastric cancer as compared with other gastric disorders. METHODS–Formalin fixed, paraffin wax embedded tissue specimens of 38 gastric cancers obtained from surgical cases were used for the immunohistochemical studies performed with the avidin-biotin complex method using monoclonal antibodies against purified pepsinogen I and II. Pepsinogen concentrations from serum obtained from the above patients, from patients with various other gastric disorders, and from normal controls were measured with a rapid non-radioactive one step enzyme linked immunosorbent assay (ELISA). RESULTS–Eight of 38 (21%) and seven of 38 (18%) gastric carcinomas showed immunoreactivity to pepsinogen I and pepsinogen II, respectively, without any correlation to histological classification or differentiation. Decreased pepsinogen I concentrations and low pepsinogen I:II ratios were found specifically in cases of gastric carcinoma and polyp, in good accordance with the immunohistochemical results. CONCLUSIONS–Low serum pepsinogen I concentrations and a low pepsinogen I:II ratio are predictive of gastric neoplasia, correlating with low tissue immunoreactivity to monoclonal antibodies raised against pepsinogen I and II. For mass screening of gastric disease including carcinoma, ELISA using a one step immunoassay performed in the present study is a rapid and reliable non-radioactive method of detecting serum pepsinogen. In addition, immunohistochemical studies showed that pepsinogen production may be increased or diminished as a result of tumour histogenesis, depending on the area of origin and the processes of cell transformation and dedifferentiation.